(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article examines the parallel between the short story «Before the End of the World» by Boris Akunin and the novel The Name of the Rose by Umberto Eco. Employing various elements of postmodernism such as play, irony, and intertextuality Akunin skillfully parodies the novel of the renowned postmodernist Eco. The study analyzes the characters, symbols, and plot structures of both works, paying particular attention to symbolic images and symbolic codes. It argues that the incorporation of an «alien» authorial code contributes to the formation of a philosophical dimension within the secondary text, significantly complicating its ideological content and moving it beyond the boundaries of mass literature. The object of the research is the texts of the aforementioned works, while the subject is the system of images, symbols, narrative parallels, and cultural codes that shape the philosophical layer of the narrative. The methodological framework includes comparative-typological, intertextual, cultural-semiotic, and mythopoetic approaches. The study demonstrates that Akunin employs elements of postmodern poetics playfulness, irony, double coding, and allusiveness not as mere imitation but as a means of creative transformation of a «foreign» text. His parodic strategy toward Eco is combined with the construction of an independent semantic structure in which symbolic images and codes deepen the philosophical dimension of the detective plot. The research reveals that beneath the entertaining surface lies a multilayered semiotic model of the «world as text». The scholarly significance of the article lies in clarifying the role of intertextuality in contemporary Russian prose and expanding the understanding of the boundaries between mass and elite literature. Its practical value consists in the possibility of applying the findings in courses on literary theory, comparative literature, and the history of postmodernism.